2012
DOI: 10.1063/1.4740235
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electron scatterings on thermoelectric effect

Abstract: In this work, we employed non-equilibrium Green's function to investigate the electron transport properties in the nanowire with the presence of scatterings. The scattering mechanism is modelled by using the concept of Büttiker probe. The effect of electron scattering is analyzed under three conditions: absence of external field; with a bias voltage; and with a finite temperature difference.It is found weak and strong scatterings strength affect the electron transport in different ways. In the case of weak sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…At the optimum electron scattering, the thermoelectric power factor could be enhanced by 6-18%. 166 Another theoretical study revealed that the external perpendicular electric eld could increase the Seebeck coefficient of the bismuth telluride NWs by a factor of 2 and the enhanced ZT could reach a value as high as 3.4 at room temperature. 162 In order to investigate the effect of electric elds on nanostructures experimentally, the electric eld is usually added to the device as a gate.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…At the optimum electron scattering, the thermoelectric power factor could be enhanced by 6-18%. 166 Another theoretical study revealed that the external perpendicular electric eld could increase the Seebeck coefficient of the bismuth telluride NWs by a factor of 2 and the enhanced ZT could reach a value as high as 3.4 at room temperature. 162 In order to investigate the effect of electric elds on nanostructures experimentally, the electric eld is usually added to the device as a gate.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Secondly (in section 6.2), we investigate the influence of electron scattering on TE effect [24]. The scattering effect is modeled by using the concept of Buttiker probe.…”
Section: Chapter VI Electron Transport In Thermoelectric Devicementioning
confidence: 99%